Sort by

- Relevance
- |Time

(i+1)^

**k**= -(3^**k**) => ((1+i)/3)^**k**= -1 => ln[((1+i)/3)^**k**] = ln(-1) =>**k**ln((1+i)/3) = ln(-1) =>**k**[ (1/2...**k**/2) and the abs. v. of the right side is 3^**k**, and a power of 3 cannot be equal to a power of...2 Answers · Science & Mathematics · 06/05/2013

**k**^2 - 4k - 12 > 0**k**^2 - 6k + 2k - 12 > 0**k**(**k**- 6) + 2 (**k**- 6) > 0 (**k**- 6) (**k**+ 2) >...you can get a product greater than 0. So EITHER**k**- 6 > 0 AND**k**+ 2 > 0 (both factors are positive...1 Answers · Science & Mathematics · 22/01/2009

Question

**K**-Form (Precalc/Calculus)? The directions...6k ((((THIS 6k SHOULD BE 2k(pi) )))) 2x=(5pi)/6 + 2k(pi)**k**= 0,1 x= pi/12 +**k**(pi) x=(5pi)/12 +**k**(pi) x= pi=12, 13(pi)/12, 5(pi)/12, 17(pi...1 Answers · Science & Mathematics · 07/12/2008

(h,

**k**) Explanation: y = a*(x – h)^2 +**k**If x = h, then y = a*(h – h)^2 +**k**y = a*(0)^2 +**k**...a > 0 i.e. the parabola has upward orientation, then a +**k**>**k**. Therefore, y =**k**is the lowest...3 Answers · Science & Mathematics · 08/06/2011

...e^(kx) - e^(-kx) ] / [ e^(3x) + e^(-3x) ] When x is large and assume

**k**>= 0 sinh(kx) / cosh(3x) ≈ e^(kx) / e^(3x) = e^(x(**k**- 3)) For sinh(kx...1 Answers · Science & Mathematics · 21/02/2019

Suppose

**K**is not compact. Then, by Heine Borel theorem,**K**...since K is unbounded, for every M > 0 there is x ∈**K**such that f(x) = ||x|| > M, which shows f is a continuous unbounded...2 Answers · Science & Mathematics · 04/07/2010

Assume |

**k**−√2| < ϵ. Need to prove that | (**k**+2)/(**k**+1)−√2... from |**k**−√2| < ϵ assemble an expression for (**k**+2)/(**k**+1)−√2 |**k**−√2| < ϵ → √2−ϵ &...1 Answers · Science & Mathematics · 28/02/2013

... 6/(

**k**+1) - 1/(**k**) = 1 ← note:**k**≠ 0 or -1 or 6(**k**) - (**k**+1) = (**k**+1)(**k**) or 6k -**k**- 1 = k² +**k**or 0 = k² +**k**- 6k +**k**...4*3 ) ] / 2**k**= [ 4 ± 2√3 ) ] / 2**k**= 2 ± √3**k**= { 2 - √3, 2 + √3 }**k**~ { 0.2679, 3.7321 }3 Answers · Science & Mathematics · 11/09/2010

"Solve for

**k**in terms of**k**" doesn't make sense:**k**=**k**is obvious. I...thing and see if we can get a cleaner statement of the relationship between x and**k**: log(base2)x+log(base2)(x+5)=**k**log(base2) [x(x+5)] =**k**{by properties of...2 Answers · Science & Mathematics · 19/10/2009

This only true if

**K**is also a metric space. Otherwise there are counterexamples.... Now to prove the claim: Forward direction: Suppose**K**is compact and A = (x_n) is a sequence in**K**. We...2 Answers · Science & Mathematics · 16/10/2010

##### Ad

related to**K**